2019
DOI: 10.1021/acsami.9b06752
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Structure–Activity Correlations in a Nickel Manganese Oxide Oxygen Evolution Reaction Catalyst by Operando Ni L-Edge X-ray Absorption Spectroscopy and 2p3d Resonant Inelastic X-ray Scattering

Abstract: Herein, we report the synthesis and electrochemical oxygen evolution experiments for a graphene-supported Ni3MnO4 catalyst. The changes that occur at the Ni active sites during the electrocatalyic oxygen evolution reaction (OER) were elucidated by a combination of operando Ni L-edge X-ray absorption spectroscopy (XAS) and Ni 2p3d resonant inelastic X-ray scattering (RIXS). These data are compared to reference measurements on NiO, β-Ni­(OH)2, β-NiOOH, and γ-NiOOH. Through this comparative analysis, we are able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 62 publications
6
51
0
Order By: Relevance
“…Instead, the main absorption peak is shifted to higher photon energies and was assigned to a Ni 3+ state with a minor Ni 2+ state contribution (Figure 1d). 34 This was further supported by XPS ( Figure S1d, e). The narrow-scan Ni 2p spectrum of FeNi-NC featured a broad peak in the 2p 3/2 region at ~854.2 eV, and a relatively weak satellite located at ~861 eV indicating the Ni 2+ oxidation state ( Figure S1d).…”
Section: Synthesis Xps Xas and Stem Analysissupporting
confidence: 58%
See 2 more Smart Citations
“…Instead, the main absorption peak is shifted to higher photon energies and was assigned to a Ni 3+ state with a minor Ni 2+ state contribution (Figure 1d). 34 This was further supported by XPS ( Figure S1d, e). The narrow-scan Ni 2p spectrum of FeNi-NC featured a broad peak in the 2p 3/2 region at ~854.2 eV, and a relatively weak satellite located at ~861 eV indicating the Ni 2+ oxidation state ( Figure S1d).…”
Section: Synthesis Xps Xas and Stem Analysissupporting
confidence: 58%
“…1c and d ) revealed further details about the chemical states of Fe and Ni. 39 Fig. 1c evidences Fe 2+ and Fe 3+ to be present in both Fe–NC and FeNi–NC, while the nitrogen-coordinated motif appeared to give rise to a characteristic “double resonance” feature in the 708 to 710 eV range.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The NiCoO/γ-Al 2 O 3 catalyst was synthesized according to a previously reported protocol. 24,34 The NiO/γ-Al 2 O 3 catalyst was prepared by an adaptation of the reverse micellar method. 35 In this approach, two different aqueous mixtures were prepared by dissolving 2.3 g ammonium oxalate monohydrate and 3 g nickel acetate tetrahydrate in 15 mL demineralized water and stirring for 15 minutes.…”
Section: Nio/γ-al 2 O 3 Catalyst Synthesismentioning
confidence: 99%
“…The XANES of Ni L 3 -edge of the dry sample revealed that Ni had an oxidation state of 2+ before activation and increased to 3+ after activation suggesting the transformation of Ni to NiOOH. 31 Co had a mixed oxidation state of 2+/3+ on the surface implying that…”
Section: Main Textmentioning
confidence: 99%